Pegembangan Articulate Storyline Materi Keanekaragaman Hayati Untuk Meningkatkan Kemampuan Literasi Sains Siswa : (Developing an Articulated Storyline for Biodiversity to Improve Students' Scientific Literacy Skills) - Setyawan , Migy Hadi; Alfi , Cindya; Fatih , Mohamad (BIODIK, 2025)
The research focuses on the development of Articulate Storyline media for biodiversity material to enhance the scientific literacy skills of fourth-grade students. This learning media was developed to improve students’ scientific literacy by utilizing the interactive features available in Articulate Storyline, such as animations, interactive quizzes, and simulations. The type of research used is Research and Development (R&D), employing the ASSURE model which consists of six steps: (1) Analyze learners, (2) State objectives, (3) Select methods, media, and materials, (4) Utilize media and materials, (5) Require learner participation, and (6) Evaluate and revise. The validation results show that the media expert obtained a percentage of 94% (very valid category), the material expert 95% (very valid category), and the test item validation 100% (very valid category). Meanwhile, the N-gain score achieved 85%, which is categorized as “Effective.” Therefore, it can be concluded that the use of Articulate Storyline media for biodiversity material is effective in improving the scientific literacy skills of fourth-grade students. Abstrak. Penelitian pegembangan articulate storyline materi keanekaragaman hayati untuk meningkatkan kemampuan literasi sains siswa kelas IV. Media pembelajaran ini dikembangkan untuk meningkatkan kemampuan literasi sains siswa dengan memanfaatkan fitur-fitur interaktif yang ada pada Articulate Storyline, seperti animasi, kuis interaktif, dan simulasi. Jenis penelitian ini adalah Reasearch and Development (R&D). Penelitian dan pengembangan ini mengambil model ASSURE terdiri atas 6 langkah yakni: 1) Analyze learner, 2) State objectives, 3) Select methods, media, and materials, 4) Utilize media and materials, 5) Require learner participation, dan 6) Evaluate and revise. Hasil validasi pada persentase ahli media mendapatkan 94% (kategori sanagat valid), ahli media 95 % (kategori sangat valid) dan validasi soal tes 100% (kategori sangat valid). Sedangkan Perolehan persentase N-gain menunjukkan 85% termasuk tafsiran “Efektif”. Jadi dapat disimpulkan bahwa penggunaan Articulate Storyline materi keanekaragaman hayati efektif untuk meningkatkan literasi sains siswa kelas IV.